Peran Agama dalam Penanganan Trauma Kolektif Pasca Bencana Alam di Indonesia - Pohan, Amriansyah; Siregar, Rony Hamdani; Dasopang, Muhammad Darwis; Sihombing, Irwandi; Ali, Muttaqin Kholis (Indo-MathEdu Intellectuals Journal, 2025)
The collective trauma experienced by the community after natural disasters in Indonesia has a profound psychological impact. This research aims to explore the role of religion in the collective trauma recovery process. This study uses a literature study. This method was used to analyze literature related to the function of religion as a source of emotional, spiritual, and social support in dealing with trauma. Data analysis was carried out qualitatively by using data reduction, data presentation, and drawing conclusions. The results of the study show that religion has a significant role in post-disaster recovery through three main aspects. First, religion provides meaning and hope through spiritual beliefs, which helps individuals and communities overcome feelings of loss and uncertainty. Second, religious rituals, such as joint prayers and meaning ceremonies, are a means to strengthen community solidarity and create a safe space to express emotions. Third, religious institutions play a role in providing material assistance, spiritual counseling, and mobilizing volunteers to support the physical and mental recovery of victims. The study concludes that religion not only serves as a source of spiritual strength, but also as an effective social tool in reducing the impact of collective trauma